EP.WE.308COVID-19 and the impact on oncological surgery at a district general hospital. (28th October 2021) - Brown, Jasmine; Dick, Lachlan; Berlansky, Martin
Abstract: Introduction: Covid-19 has had a significant impact on all aspects of healthcare. Efforts to maintain oncological surgery have continued throughout the pandemic despite facing significant challenges. We aimed to characterise our experience of oncological surgery during the first 2-months of the pandemic in Scotland and compare that with the same period in 2019. Methods: A prospective cohort study was performed from 23/03/20 to 07/05/20. All elective oncological operations at a single district general hospital, predominantly managing breast and colorectal malignancies, were included. Data on patient demographics, waiting time to surgery, inpatient characteristics and oncological outcomes were recorded. Statistical analysis was used to compare these with retrospective data from 2019. Results: A total of 37 patients were included, 18 in 2019 and 19 in 2020. There were no differences in patient age (63 vs 66.2 years, p = 0.486), length of stay (5.3 vs 4.3 days, p = 0.697) time spent on waiting list (25.4 vs 20.9 days, p = 0.303) or surgical approach (p = 0.300). Oncological outcomes were comparable with no statistical difference in clear resection margin status (88.9 vs 84.2%, p = 0.189) or positive nodal status (5.6 vs 26.3%, p = 0.086). No patient in either cohort had a post-operative complication. Conclusion: Oncological surgery during Covid-19 can be performed safely and with favourable oncological outcomes. The longer-term effects from delayed diagnoses remain to be evaluated.